Immune Evasion Mechanisms of Staphylococcus epidermidis Biofilm Infection - Le, Katherine Y.; Park, Matthew D.; Otto, Michael (Frontiers in Microbiology, 2018)
The primary virulence factor of the skin commensal and opportunistic pathogen, Staphylococcus epidermidis, is the ability to form biofilms on surfaces of implanted materials. Much of this microorganism’s pathogenic success has been attributed to its ability to evade the innate immune system. The primary defense against Staphylococcus epidermidis biofilm infection consists of complement activation, recruitment and subsequent killing of the pathogen by effector cells. Among pathogen-derived factors, the biofilm exopolysaccharide polysaccharide intercellular adhesion (PIA), as well as the accumulation-associated protein (Aap), and the extracellular matrix binding protein (Embp) have been shown to modulate effector cell-mediated killing of S. epidermidis. Phenol-soluble modulins (PSMs) constitute the only class of secreted toxins by S. epidermidis, at least one type of which (PSM) possesses strong cytolytic properties toward leukocytes. However, through selective production of non-cytolytic subtypes of PSMs, S. epidermidis is able to maintain a low inflammatory infection profile and avoid eradication by the host immune system. Taken together, our emerging understanding of the mechanisms behind immune modulation by S. epidermidis elucidates the microorganism’s success in the initial colonization of device surfaces as well as the maintenance of a chronic and indolent course of biofilm infection.